2021
DOI: 10.1021/acssuschemeng.1c06112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Keratin on Epoxidized Linseed Oil Curing and Thermoset Performances

Abstract: Keratin, a valuable protein obtained from chicken feather waste from the food industry, was used in this study in combination with a biobased formulation of epoxidized linseed oil (ELO) and dodecenylsuccinic anhydride (DDSA). The influence of keratin on the ELO cross-linking reaction was studied using differential scanning calorimetry (DSC) and in situ Fourier transform infrared (FT-IR) spectroscopy, showing the chemical contribution of the protein during network formation. Moreover, keratin showed a positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…2a). 31 For the polymer PIBQ and the corresponding composite PIBQ-1%rGO, it can be found that the strength of these three peaks significantly decreases (Fig. 2a and b), implying the occurrence between the amine unit and the anhydride unit.…”
Section: Resultsmentioning
confidence: 93%
“…2a). 31 For the polymer PIBQ and the corresponding composite PIBQ-1%rGO, it can be found that the strength of these three peaks significantly decreases (Fig. 2a and b), implying the occurrence between the amine unit and the anhydride unit.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, the tan δ peaks of the resins based on AESO and AEHO ( Figure S7b ) are broader than those of AELO-based samples, highlighting a more heterogeneity of crosslinked systems [ 19 , 47 , 48 , 49 ]. In particular, this behaviour indicates that the length of the chain segments between the crosslinks is larger in AESO-based and AEHO-based resins than to AELO-based materials [ 50 ]. This result suggests that the resins based on linseed oil present a more rigid structure and higher crosslinking density associated with a reduced free volume.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the most recent work on epoxidized vegetable oil thermosets and composites include the development of recyclable and reprocessable thermosets and hybrid composites with incorporation of lignocellulosic biomass derived fillers. ,,, It is necessary that we discuss the research reported by Mija and co-workers whose scientific contribution pioneered reprocessable thermosets from epoxidized vegetable oil. The EVOs synthesized were copolymerized with anhydrides and reinforced by natural fillers and fibers up to 30 wt % (chicken feather wastes, humins, spruce bark powder, lignin, hydrocarbon biomass. The optimized composites fabricated demonstrated tensile strength of up to 12 MPa, and tensile modulus ranged between 100 and 800 MPa). Further, a dicarboxylic acid (dithiodibenzoic acid) was used as curing agent with dithiol moieties enabling dynamic reversible bonds under external stimuli like heat and pressure, and later, flax fibers were also used for fabricated biocomposites.…”
Section: Epoxidized Vegetable Oils In Thermosets and Compositesmentioning
confidence: 99%